PEMANFAATAN GAS IKUTAN : TEROBOSAN EKONOMI DAN UPAYA UNTUK MENURUNKAN EMISI GAS RUMAH KACA PADA PERUSAHAAN MIGAS - Zulkifli Rangkuti (PSTE UNIMUS, 2010)
Flaring gas industry is profitable for community and government, in term of economy and environment (sustainable). The investation of that industry, haye to study if economically feseable to be develop and environmentally friendly, so we need to study about feasibility study and environment impact assessment. The aim of this study to examines feasibitity study and environment benefit. For this purposes, the analysis were used in this study Net present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), and profitability Index analysis. Result of this study were flaring gas industry in this study feasible and enviroimentally (cleaner production), and feasible to develop. Flaring gas industry had positif net present value with net profit (NPV) US 1.148.174,00 and had recoupery to bank higher than bank interest rate, and the ability to restore the bank loan capital until the time limit, total IRR 14,42 %. Payback investment of this company is 5,080 years and payback loan is 3,537 years. This means, that capital payback period paster than contract period and began fifth years and so on, (break even point in fifth years). Starting in the sixth years, this company will be profit, because payback period shorter than contract period (10 years). It's indicates that present value of net cash receipts, in the future is greater than the present value of investment, so that is profitable. By the way this company should pay for environmental protection and social costs, but in this study has not been taken in to account. Flaring gas industry not only profitable, but become one of the efforts to reduce emission. This industry relatively not pollute the environment and environmentally friendly. Keywords: feasibility, flaring gas, industry, NPV, IRR, PBP, emission